Context and the evidence‐based paradigm: The potential for participatory research and systems thinking in oral health. Issue 1 (19th August 2020) - Brocklehurst, Paul R.; Baker, Sarah R.; Langley, Joe
Abstract: The implementation of research evidence to promote oral health is critical, given the intransigent and emerging challenges for policymakers at a population level. Despite this, little attention has been paid to implementation research within the evidence‐based paradigm. This is important as getting research evidence into clinical practice is not a linear path that consists of simple sequential steps. In this article, we argue that we need to consider a broader range of conceptual and methodological approaches to increase the value of information generated. This should be undertaken either in parallel with empirical and experimental designs, or in some cases, instead of. This is important if we are going to understand the complexity and contextual knowledge of the 'system', within which interventions are implemented. Involving key stakeholders alongside empirical and experimental designs is one helpful approach. Examples of these approaches include Patient and Public Involvement and the development of Core Outcome Sets, where the views of those that will be potentially affected by the research, are included. The use of theoretical frameworks and process evaluations alongside trials are also important, if they are fully integrated into the approach taken to address the research question. A more radical approach is using participatory designs and 'systems thinking'. Participatory approaches include subject matter 'experts by experience'. These include patients, their families, carers, healthcare professionals, services managers, policymakers, commissioners and researchers. Participatory approaches raise important questions about who facilitates the process, when it should happen and how the diverse actors become meaningfully engaged so that their involvement is active, democratic and ongoing. We argue that the issues of control, power and language are central to this and represent a paradigmatic shift to conventional approaches. Systems thinking captures the idea that public health problems commonly involve multiple interdependent and interconnected factors, which interact with each other dynamically. This approach challenges the simplicity of the hierarchy of evidence and linear sequential logic, when it does not account for context. In contrast, systems thinking accepts complexity de novo and emphasizes the need to understand the whole system rather than its individual component parts. We conclude with the idea that participatory and systems thinking help to unpack the diverse agents that are often involved in the generation and translation of evidence into clinical dental practice. It moves our conception of research away from a simple exchange between 'knowledge producers' and 'knowledge users' and raises both methodological and epistemological challenges.